Legal Counseling Law Number 30 of 1999 About Arbitration And Alternative Dispute Resolution In Nendali Village, East Sentani District Jayapura Regency - Daniel Tanati; James Yoseph Palenewen; Yustus Pondayar; Elias Hence Thesia; Marthinus Solossa; Johan Rongalaha (Amirul Bangun Bangsa, 2023)
This service was carried out under the title Legal Counseling Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution in Nendali Village, East Sentani District, Jayapura Regency, activities carried out for partners due to cases from partners regarding misunderstanding regarding the resolution of customary land disputes based on statutory regulations. the invitation is valid and where the parties to the dispute do not want to give in or want to win on their own so that with the expertise they have, the service can carry out legal counseling so that the parties in the dispute can know about the existence of laws and regulations that regulate non-violent dispute resolution. litigation/outside of court. The method of implementing this service is carried out by applying science and technology through lectures and discussions held on Saturday 29 July 2023, at the Nendali Village Hall as well as providing assistance to partners in providing knowledge about Alternative Dispute Resolution (ADR) based on Law Number 30 of 1999 The output of this service is to provide partners with an understanding of the things that cause customary land disputes between one village and another and to provide legal assistance to partners to resolve customary land boundary disputes within customary law communities based on existing laws and regulations. applies.